Antarctica on the International Court of Justice: 60 year after the cases Union Kingdom v. Chile and Union Kingdom v. Argentina - Ferrada Walker, Luis Valentín (Revista Tribuna Internacional, 2015)
The applications presented in relation with the sovereignty over the Antarctica by the United Kingdom on International Court of Justice against Chile and against Argentina in 1955 are analyzed. The documents delivered during the process are also revised. The defendants States were not prepared to accept the Court jurisdiction; therefore both causes were definitely retired from the list without resolve about the dispute. Nevertheless, it seems relevant to consider these cases to know the grounds on which the implicated States and specially the United Kingdom support their Antarctic sovereignty and also to understand that at the end the Chilean and Argentinian attitude helped on the process that will finish few years later with the signature of the Antarctic Treaty.